A Unique One-Time Password Table Sequence Pattern Authentication: Application to Bicol University Union of Federated Faculty Association, Inc. (BUUFFAI) eVoting System - Balilo Jr., Benedicto B.; Gerardo, Bobby D.; Medina, Ruji P.; Byun, Yungcheol (International Journal of Computing Sciences Research, 2017)
Purpose – Electronic Voting System (EVS) is a type of voting program that deals primarily with the selection, the casting of votes with embedded security mechanism that detects errors, and the tamper-proof election of results done through the use of an electronic system. It can include optical scan, specialized voting kiosks and Internet voting approach. Most organizations have difficulties when it comes to voting and the Bicol University Union of Federated Faculty Association Incorporated (BUUFFAI) is not an exception. Some of the problems involved include convenience, cost, geographical location of the polling precinct, and voting turnouts. Method – This study extends the scope of the current BUUFFAI eVoting system to address such issues and to eliminate inconvenience both to the faculty voters and the facilitators. This voting scheme used an algorithmic OTP scheme based on table sequence pattern schedule that randomly generates an XY coordinate unique to voters that will be sent to voter registered email address. Results – This study addressed the security requirements and maintained election procedures with confidentiality, integrity and availability.